An Assessment of Derelict Building Constructions Situated In Coastal Regions - Rahman, Mohammad Junaedy; Hasrul, Muhammad Reza; Ashad, Hanafi; Yusuf, Furqan Ali; Hasrul, Nur Refera (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2024)
Reinforced concrete structures constructed in coastal areas in Indonesia often suffer damage before reaching their intended service life, with steel reinforcement corrosion being a major contributing factor. This study aims to investigate the use of concrete structures produced with simple methods and inadequate supervision in coastal regions. Reinforced concrete structures near the coast are susceptible to carbonation due to marine environmental factors, leading to reinforcement corrosion. The study was conducted on the Dande Dandere Market building, Tanakeke Island, Takalar Regency, South Sulawesi. The research method employed quantitative techniques, including surveys and structural testing. Visual inspections were conducted to identify the types of damage present in the building and estimate their causes. Structural testing involved both destructive and non-destructive tests. Concrete compressive strength testing was also conducted to assess the concrete sample’s compressive strength, along with carbonation testing to determine the acidity level of concrete due to the intrusion of salt compounds or carbonation formed within the concrete mass. The research findings indicate structural degradation in the market’s construction, occurring more rapidly than the intended lifespan of the building. Signs of structural degradation in the reinforced concrete construction include spalling of concrete cover on beams, supporting columns, and cantileverslabs, as well as degraded reinforcement, with an average reduction in steel weight of 62.70% over six years, and an average weight loss of 0.103 grams per day. Therefore, efforts are needed to optimize the structural quality of the building through comprehensive repairs, starting from the foundation. However, for cost-efficient alternatives, it is recommended to use timber structural materials for new market construction. The use of timber in coastal buildings, which are vulnerable to marine influences, is more feasible as the presence of saltwater can inhibit wood decay caused by microorganisms.